2003
DOI: 10.1128/jb.185.23.6995-7000.2003
|View full text |Cite
|
Sign up to set email alerts
|

Anabaena sp. Strain PCC 7120 hetY Gene Influences Heterocyst Development

Abstract: The filamentous cyanobacterium Anabaena (Nostoc) sp. strain PCC 7120 responds to starvation for fixed nitrogen by producing a semiregular pattern of nitrogen-fixing cells called heterocysts. Overexpression of the hetY gene partially suppressed heterocyst formation, resulting in an abnormal heterocyst pattern. Inactivation of hetY increased the time required for heterocyst maturation and caused defects in heterocyst morphology. The 489-bp hetY gene (alr2300), which is adjacent to patS (asl2301), encodes a prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The patS gene from Anabaena PCC 7120 ( asl2301 ) is preceded by two genes ( all2302 and all2303 ) encoding proteins annotated as patatin and dihydroorotase respectively. On the downstream side is a gene ( alr2300 ) annotated as hetY , encoding a protein described as necessary for timely heterocyst differentiation (Yoon et al ., ). We found 28 genomes, all from heterocyst‐forming cyanobacteria, that have a short RGSGR‐containing ORF situated near at least one of the typical upstream or downstream genes (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The patS gene from Anabaena PCC 7120 ( asl2301 ) is preceded by two genes ( all2302 and all2303 ) encoding proteins annotated as patatin and dihydroorotase respectively. On the downstream side is a gene ( alr2300 ) annotated as hetY , encoding a protein described as necessary for timely heterocyst differentiation (Yoon et al ., ). We found 28 genomes, all from heterocyst‐forming cyanobacteria, that have a short RGSGR‐containing ORF situated near at least one of the typical upstream or downstream genes (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…ubks were described as being essential genes in S. pneumoniae (Zalacain et al, 2003; Havarstein et al, 2006), B. subtilis (Kobayashi et al, 2003), Mycoplasma pulmonis (French et al, 2008) and E. coli (Freiberg et al, 2001; Campbell et al, 2007) On the other hand, other studies have concluded that ubk would be dispensable in S. pneumoniae (Molzen et al, 2011), B. subtilis (Hunt et al, 2006; Karst et al, 2009; Nguyen et al, 2017), and Anabaena sp. strain (Yoon et al, 2003). One can therefore not exclude that these opposing observations either convey the presence of suppressive mutations appearing when deleting ubk genes or that the dispensability/essentiality of ubk is strain-specific.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the yjeE gene is essential for the viability not only of E. coli (3,5,17) but probably also Salmonella enterica (36), Fransicella novicida (18), and Streptococcus pneumoniae (71), although it is dispensable for the survival of Staphylococcus aureus (71), Anabaena (68), and Bacillus subtilis (reference 27, correcting the earlier study in reference 37). The cellular function of YjeE is not known, although loss of yjeE resulted in aberrant heterocyst development in Anabaena (68). Based on the observation that yjeE genes are absent from the genomes of some Mycoplasma and Ureaplasma species, which lack cell walls, together with the fact that yjeE is found in an operon with a gene encoding a cell wall amidase in some gram-negative bacteria, it has been proposed that YjeE plays a role in cell wall biogenesis (60).…”
mentioning
confidence: 99%
“…The elucidation of a high-resolution X-ray crystal structure of YjeE of Haemophilus influenzae, coupled with biochemical analysis of the E. coli protein, has shown that it is a typical P-loop ATPase that binds and hydrolyzes ATP, leading to speculation that it may act as a hydrolysis-driven molecular switch (3,60). Studies have shown that the yjeE gene is essential for the viability not only of E. coli (3,5,17) but probably also Salmonella enterica (36), Fransicella novicida (18), and Streptococcus pneumoniae (71), although it is dispensable for the survival of Staphylococcus aureus (71), Anabaena (68), and Bacillus subtilis (reference 27, correcting the earlier study in reference 37). The cellular function of YjeE is not known, although loss of yjeE resulted in aberrant heterocyst development in Anabaena (68).…”
mentioning
confidence: 99%